Maturity indices for acid lime (Citrus aurantifolia) cultivar 'Kagzi' grown in central India - LADANIYA, M S; SINGH, SHYAM (The Indian Journal of Agricultural Sciences, 2013)
Maturity indices of acid iime fruit cuitivar Kagzi (Citrus aurantifolia Swingle) were standardized for agroelimaticconditions of central fndia. Fruit weight, volume and juice content increased significantly up to 160 days from anthesis.The respiration rate dropped from 159.65-80.11 mg CO2/kg/hr during maturation. Peel colour changed from dark green (after 120 days) to greenish-yellow (after 160 days) with increase in brightness (L value) and colour intcnsity (chroma) and decrease in hue angle (115.630 after 120 days to 90.710 after 160 days). Height/diameter ratio decreased from 1.08 (after 140 days) to 1.02 (after 160 days) with round shape of fruit at maturity. Peel thickness decreased while firmness remained unchanged. Juice pH decreased with maturity. Acidity increased alongwith total soluble solids up to 150 clays with slight decline after 160 days. Ascorbic acid content was highest (58.08 mg/ 100 ml) after 150 days and declined to 53.00 mg/ 100 ml after 160 days. Maturity period of 160 days from anthesis and juice content of 48 with 8.00% acidity were suggested as indices for harvesting.